Temperature-depth curves and heat flow in central part of Anatolia, Turkey - ERKAN, KAMİL (ELSEVIER, 2019)
The objective of this study is to determine the crustal thermal regime of Central Anatolia Province and its relationship with regional tectonics. Investigations include new temperature-depth measurements in wells, calculations of geothermal gradients from new and previously measured temperature logs, and determinations of heat flow with terrain corrections if necessary. The results provide us with a better understanding of the regional distribution of subsurface temperatures and heat flow within the study area. Although Central Anatolia Province is bordered with tectonically active areas, moderate heat flow values (64 +/- 16 mW m(-2)) are generally observed within the region in accordance with the relatively less tectonic activity. Two thermally anomalous zones are indicated in the vicinity of Kirsehir and Kizilcahamam with heat flow values of higher than 100 mW m(-2). Anomalous heat flow in these areas can best be explained by high radioactivity of basement rocks although this is not directly confirmed for the Kizilcahamam anomaly. The high elevation and recent volcanic activity in the region indicate that thermal activity may be present at lithospheric levels but have not yet reached up to crustal levels. Also, no surface heat flow anomaly due to fault activity was observed at the section of the North Anatolia fault within the study area.
Keywords: Heat flow; Geothermal gradient; Central Anatolia; SOUTHERN MARGIN; GRANITOIDS; WESTERN; UPLIFT; PLATEAU; AFRICAN; REGION; FIELD; AGES